A Note on Stand Dynamics of Antiaris toxicaria (Pers.) Lesch., a Rare Plant of Konkan Region of Western Ghats - Mirgal, A.B; Rane, A.D.; Gunaga, Rajesh P.; Narkhede, S.S.; Bhave, S.G. (Indian Forester, 2013)
No Abstract